Unveiling Charge‐Transport Mechanisms in Electronic Devices Based on Defect‐Engineered MoS2 Covalent Networks (Adv. Mater. 15/2023). Issue 15 (13th April 2023) - Ippolito, Stefano; Urban, Francesca; Zheng, Wenhao; Mazzarisi, Onofrio; Valentini, Cataldo; Kelly, Adam G.; Gali, Sai Manoj; Bonn, Mischa; Beljonne, David; Corberi, Federico; Coleman, Jonathan N.; Wang, Hai I.; et al.
Abstract : Charge‐Transport Mechanisms A multiscale investigation of the charge‐transport mechanisms in covalently interconnected networks of MoS2 nanosheets is presented by Paolo Samorì and co‐workers in article number 2211157 . The chemical structure of the dithiolated bridging linker is critical, with π‐conjugated systems outperforming aliphatic molecules thereby boosting interflake transport. These findings highlight the great potential of defect engineering for the fabrication of high‐performance MoS2 devices.